2019
DOI: 10.1111/febs.15143
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells and organ function: applications and implications of understanding unique and reciprocal remodelling

Abstract: The microvasculature is a heterogeneous, dynamic and versatile component of the systemic circulation, with a unique ability to locally self‐regulate and to respond to organ demand and environmental stimuli. Endothelial cells from different organs display considerable variation, but it is currently unclear to what extent functional properties of organ‐specific endothelial cells are intrinsic, acquired and/or reprogrammable. Vascular function is a fundamental pillar of homeostasis, and dysfunction results in sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 115 publications
0
26
0
Order By: Relevance
“…Importantly, cell senescence is associated with an inflammatory microenvironment ( Coppé et al, 2008 ; Kuilman et al, 2008 ; Wajapeyee et al, 2008 ), identified in epirubicin-treated hUVEC conditioned medium ( Figures 2C,D ). The effects of inflammation in vascular function are notably reciprocal, and associated with a myriad of chronic health conditions, such as diabetes, aging and neurodegeneration and multiple respiratory syndromes ( Augustin and Koh, 2017 ; Reiterer and Branco, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, cell senescence is associated with an inflammatory microenvironment ( Coppé et al, 2008 ; Kuilman et al, 2008 ; Wajapeyee et al, 2008 ), identified in epirubicin-treated hUVEC conditioned medium ( Figures 2C,D ). The effects of inflammation in vascular function are notably reciprocal, and associated with a myriad of chronic health conditions, such as diabetes, aging and neurodegeneration and multiple respiratory syndromes ( Augustin and Koh, 2017 ; Reiterer and Branco, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human umbilical vein EC (hUVEC) were used to investigate effects on EC survival and function. Additionally, naïve (tumor-free) mice were treated with intravenous epirubicin to assess effects of treatment on lung vascular parameters, considering that lung disease and associated comorbidities are heavily associated with vascular dysfunction ( Reiterer and Branco, 2020 ), and this is also a common metastatic site. Primary microvascular EC (MVEC) were also isolated from lung tissue ( Reiterer et al, 2019 ) to investigate the effects of epirubicin on EC behavior following in vivo exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, cell senescence is associated with an inflammatory microenvironment (Coppé, Patil et al 2008, Kuilman, Michaloglou et al 2008, Wajapeyee, Serra et al 2008, identified in epirubicin-treated hUVEC conditioned medium (Figure 2C, D). The effects of inflammation in vascular function are notably reciprocal, and associated with a myriad of chronic health conditions, such as diabetes, ageing and neurodegeneration and multiple respiratory syndromes (Augustin andKoh 2017, Reiterer andBranco 2020).…”
Section: Discussionmentioning
confidence: 99%
“…EC form a continuous but very heterogeneous organ, with unique functional and metabolic profiles, which responds to stress and inflammation in an organ-specific manner [50]; this may actually underlie therapy-driven metastatic organotropism. Most studies investigating vascular damage in response to prolonged exposure to chemotherapy use HUVECs as their model, which does not address the impact on organ function in light of microvascular heterogeneity [51]. For example, expression of genes involved in substrate transport, ECM remodelling, barrier function and endothelial activation, are significantly altered following doxorubicin exposure [52], but their baseline expression varies significantly across the microvascular EC of the brain, lung and heart [50]-the first two are common metastatic organs for TNBC [53], and the cardiac microvascular EC perform essential roles in cardiac muscle function [54].…”
Section: Relapsementioning
confidence: 99%
“…While microvascular cell plasticity ensures that metabolic demands are met at specific organs and in specific contexts [64], their adaptive responses to stress can involve structural, angiogenic, intercellular communication and metabolic changes likely to favour dissemination and proliferation of circulating tumour cells (CTC) [48,51,[65][66][67]. In turn, CTC have been shown to more efficiently evade cytotoxic treatments, as a result of enhanced DNA repair mechanisms [68].…”
Section: Relapsementioning
confidence: 99%